Fantasy and Identity in Critical Political Theory - Glynos, Jason (Filozofski vestnik, 2012)
In this essay I explore the appeal of the psychoanalytic category of fantasy for critical political theory, by which I mean a theory grounded in a political ontology that offers a rationale for both normative and ideological critique. I draw on the work of William Connolly, Susan Faludi, Jacqueline Rose, and Judith Butler, among others, to consider the explanatory and critical implications of the concept of fantasy for questions of identity, and political identity in particular. I argue that fantasy is a useful device with which to explore and probe the political and ideological aspects of a practice or narrative because it foregrounds the combined significance of the symbolic and affective dimensions of life. Moreover, a psychoanalytic perspective can facilitate a move away from an epistemological or moralizing understanding of fantasy and political identity, shifting the emphasis instead toward a more ontological and ethical understanding.